An Overview of Intellectual Property Rights as Waqf in Indonesia and Malaysia - Yuswar, Cheryl Patriana; Runtung; Maulana, Insan Budi; Azwar, T. Keizerina Devi (Ultimate Journal of Legal Studies, 2023)
This paper aims to get an overview of Intellectual Property Rights as waqf in Indonesia and Malaysia. To achieve these goals, the research uses a normative legal writing method with descriptive-analytical specifications. The findings reveal, both Indonesia and Malaysia permit IPR being waqf. Unfortunately, there are no implementing regulation or specific guidelines regarding how and what to waqf from IPR in both states. The absence of implementing regulation or guideline will have implication not only for confusion in the community, but also for the lack of applicability of IPR being waqf in the community.